2003
DOI: 10.1172/jci200316738
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of cardiomyocyte dysfunction by phospholamban ablation does not prevent ventricular failure in genetic hypertrophy

Abstract: Cardiac hypertrophy, either compensated or decompensated, is associated with cardiomyocyte contractile dysfunction from depressed sarcoplasmic reticulum (SR) Ca(2+) cycling. Normalization of Ca(2+) cycling by ablation or inhibition of the SR inhibitor phospholamban (PLN) has prevented cardiac failure in experimental dilated cardiomyopathy and is a promising therapeutic approach for human heart failure. However, the potential benefits of restoring SR function on primary cardiac hypertrophy, a common antecedent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…No effect of PLN ablation on echocardiographic measures of hypertrophy and dysfunction were observed in either model, and impaired hemodynamic responsiveness to β-adrenergic stimulation was not affected (14). These findings contrast with those of our previous study on PLN ablation in MLP cardiomyopathic mice (using a similar crossbreeding approach), in which the cardiomyopathic phenotype did not develop (12), and they also differ from the present findings in the adult rat with MI, in which an entirely different approach was used to achieve PLN inhibition in the presence of established cardiac dysfunction and dilation.…”
Section: Figurementioning
confidence: 81%
See 3 more Smart Citations
“…No effect of PLN ablation on echocardiographic measures of hypertrophy and dysfunction were observed in either model, and impaired hemodynamic responsiveness to β-adrenergic stimulation was not affected (14). These findings contrast with those of our previous study on PLN ablation in MLP cardiomyopathic mice (using a similar crossbreeding approach), in which the cardiomyopathic phenotype did not develop (12), and they also differ from the present findings in the adult rat with MI, in which an entirely different approach was used to achieve PLN inhibition in the presence of established cardiac dysfunction and dilation.…”
Section: Figurementioning
confidence: 81%
“…In a recent report, the effects of PLN ablation, produced by crossbreeding with PLN-null mice, were assessed in two genetic mouse models, Gαq overexpression and targeted mutation of myosin-binding protein C, both of which exhibited extensive cardiomyopathic changes associated with the development of cardiac dysfunction and dilation (14). No effect of PLN ablation on echocardiographic measures of hypertrophy and dysfunction were observed in either model, and impaired hemodynamic responsiveness to β-adrenergic stimulation was not affected (14).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first instance of a human equivalent of the PLN-null mouse. The apparent pathological effects of absent PLN in human hearts contrast strikingly with benefits observed in many, although not all (39), mouse heart failure models. These data emphasize a general concern that targeted therapies whose design is based exclusively on results of studies in rodent models, in which phenotypes can differ radically from those observed in the corresponding human genetic condition, may not ultimately be successful in human disease.…”
mentioning
confidence: 77%